Of loves and crimes. Class and gender representations in Chilean nocturnal police telenovelas - Antezana Barrios, Lorena (2023)
Based on the narrative, televisual and hermeneutical analysis of three successful Chilean night-time soap operas of the police subgenre, Alguien te mira (Rencoret, 2007), ¿Dónde está Elisa? (Demicheli & Campos, 2009) and El laberinto de Alicia (Demicheli & Aguirre, 2011), this article wonders about the gender representations that these stories offer us. The results indicate that these soap operas are a hybrid product that combines classic melodrama with detective story. Unlike daytime and evening productions, the protagonists here are from the upper class, the story is fast-paced and dynamic, and plays with secrecy and suspense. However, in a gender reading, it can be seen that, although women are initially presented as autonomous, independent and empowered, they finally end up fulfilling a classic role: that of mothers.